2007
DOI: 10.1002/aoc.1225
|View full text |Cite
|
Sign up to set email alerts
|

Three‐step synthesis of arylpolyboronic acids from phenols via organotin compounds

Abstract: In this paper we describe a three‐step synthesis of aryldi‐ and triboronic acids starting from phenols. Several substituted phenols (I) were converted into the corresponding aryldiethylphosphates (II) in good to excellent yields. The latter, on reaction with sodium trimethylstannide in liquid ammonia, under irradiation, afforded the aryl‐ and heteroarylpoly(trimethylstannyl) derivatives in 65–90% yield. The third step is the reaction of the organotin compounds with borane in THF, which leads to the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In preliminary studies, the analysis by 119 Sn-NMR of the crude mixture obtained in this reaction showed the formation of 4 together with tri-n-butyltin bromide (5). However, after passing a solution of the crude product in ethyl acetate through a chromatographic column with silica gel doped with 10% of KF compound 4 was obtained pure.…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…In preliminary studies, the analysis by 119 Sn-NMR of the crude mixture obtained in this reaction showed the formation of 4 together with tri-n-butyltin bromide (5). However, after passing a solution of the crude product in ethyl acetate through a chromatographic column with silica gel doped with 10% of KF compound 4 was obtained pure.…”
Section: Methodsmentioning
confidence: 88%
“…Sn-NMR spectrum of the crude products before the treatment with silica gel doped with KF was also observed the formation of tri-n-butyltin bromide (5).…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 2 more Smart Citations
“…Consequently, a variety of arylpolyboronic acids is achievable from the stannanes previously synthesized by the S RN 1 mechanism from ArCl or ArOH in around 80% yields [50,51]. Consequently, a variety of arylpolyboronic acids is achievable from the stannanes previously synthesized by the S RN 1 mechanism from ArCl or ArOH in around 80% yields [50,51].…”
Section: Consecutive S Rn 1-pd(0)-catalyzed Crosscoupling Reactionsmentioning
confidence: 99%